The Role and Place of Covid-19: An Opportunistic Avenue for Exponential World’s Upsurge in Cyber Crime - Angel Olofinbiyi, Sogo (2022)
An evidence-based analysis of COVID-19 suggests that the ailment is a bio-medically inclined natural mystic blowing through the world. To this end, this study focuses solely on the role the pandemic plays as an outbreak of cybercrime vector. The study presents a number of the world’s most recent cyber insecurity cases that accompanied the onset of the pandemic and findings were discussed within the context of situational opportunity theory of crime. It provides a framework for emergency management approach to protect global citizens and institutions from cyberattacks, as well as, mitigating the outbreak of the crime being propagated by the presence of the novel virus. Global sensitization and awareness programmes across various communities on the potential dangers of cyber insecurity accompanying the COVID-19 pandemic should be helpful. Of most significance, the fight against the invisible warfare should continue with high spirits of relentlessness until absolute peace, relief, resilience and normalcy are able to take root in the global communities